2019
DOI: 10.1093/bioinformatics/btz267
|View full text |Cite
|
Sign up to set email alerts
|

Is the Bombali virus pathogenic in humans?

Abstract: Motivation The potential of the Bombali virus, a novel Ebolavirus, to cause disease in humans remains unknown. We have previously identified potential determinants of Ebolavirus pathogenicity in humans by analysing the amino acid positions that are differentially conserved (specificity determining positions; SDPs) between human pathogenic Ebolaviruses and the non-pathogenic Reston virus. Here, we include the many Ebolavirus genome sequences that have since become available into our analysis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Potential determinants of Ebolavirus pathogenicity in humans were identified by analyzing the differentially conserved amino acid positions called specificity determining positions (SDPs) between human pathogenic ebolaviruses and the non-pathogenic Reston virus [25]. Recently, this study was extended to include BOMV to assess its pathogenicity to humans [26]. At SDPs, BOMV shared the majority of amino acids (63.25%) with the human pathogenic Ebolaviruses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential determinants of Ebolavirus pathogenicity in humans were identified by analyzing the differentially conserved amino acid positions called specificity determining positions (SDPs) between human pathogenic ebolaviruses and the non-pathogenic Reston virus [25]. Recently, this study was extended to include BOMV to assess its pathogenicity to humans [26]. At SDPs, BOMV shared the majority of amino acids (63.25%) with the human pathogenic Ebolaviruses.…”
Section: Introductionmentioning
confidence: 99%
“…However, for two SDPs in viral protein 24 (VP24), which may be critical for the lack of Reston virus human pathogenicity, the BOMV amino acids match those of Reston virus. Thus, BOMV may not be pathogenic in humans [25, 26]. Nonetheless, rRT-PCR assays are important for biosurveillance of BOMV and other potential new variants in the wild.…”
Section: Introductionmentioning
confidence: 99%
“…However, the omeprazole 364 concentrations that interfered with SARS-CoV-2 CPE formation (IC50 34µM) was 365 beyond therapeutic omeprazole plasma concentrations reported to reach about 8µM 366 [Shin & Kim, 2013]. We have recently shown that omeprazole increases the antiviral 367 activity of acyclovir [Michaelis et al, 2019]. Here, we combined both aprotinin and 368 remdesivir with a fixed omeprazole concentration of 8µM, which resulted in further 369 increased activity against CPE formation (aprotinin 2.7-fold, remdesivir 10-fold) 370…”
mentioning
confidence: 98%
“…In contrast, Reston virus (RESTV) does not cause disease in humans but does cause serious, often lethal disease in NHPs, specifically cynomolgus macaques (Macaca fascicularis) [4]. Although studies have demonstrated that the glycoprotein (GP) of the recently identified Bombali virus (BOMV) is capable of mediating entry into human cells, it is not yet known whether BOMV can cause disease in humans [5][6][7]. Lastly, there has been only a single reported case of Taï Forest virus (TAFV) in humans, which occurred in 1994 in Côte-d'Ivoire when a 34-year-old veterinarian became ill after performing an autopsy on a wild chimpanzee found in the Taï Forest [8][9][10].…”
Section: Introductionmentioning
confidence: 99%